Prospective study on changes in the donor gallbladder contraction function after left lateral lobe hepatectomy. (5th June 2019) - Wei, Lin; Zhi, Xin; He, Enhui; Qian, Linxue; Sun, Liying; Zhu, Zhijun; Zeng, Zhigui; Qu, Wei
Abstract: This study aimed to evaluate the feasibility of donor gallbladder preservation in liver transplantation. Conventional removal of the donor gallbladder is applied in a majority of pediatric liver transplantation. A total of 42 donors who underwent gallbladder preservation in liver transplantation from October 2013 to December 2015 at the Beijing Friendship Hospital, China, were enrolled for the study. The changes in gallbladder volume and the gallbladder EF of donors before and after surgery were measured through ultrasound, and the changes in the donor gallbladder contraction function before and after surgery were evaluated to help verify the feasibility of gallbladder preservation in living donor left lateral lobe hepatectomy. The gallbladder emptying index dropped to 42.67% in 2 weeks after surgery and gradually increased with the length of recovery time, which could reach 69.14% in 3 months after surgery. At that time, 97.6% of the donors were considered to have recovered their gallbladder contraction function. The gallbladder contraction function at an early stage after gallbladder preservation in liver transplantation is not obviously improved, but it can recover to a normal level in 1 month after surgery, indicating that the gallbladder preservation in hepatectomy of living donor can effectively guarantee the gallbladder contraction function.